SIMULASI MODEL REAL OPTION ANALYSIS PADA KEGIATAN PENAMBANGAN NIKEL : PENDEKATAN LEAST SQUARE MONTE CARLO - Ismail, Ardhan
Nickel is considered to be one of the most important mining commodity due to its role in the stainless steel industry and therefore our daily life. The demand for high and low grade nickel has risen, affecting the project value of companies. The project value of a mining company could be evaluated economically by using the Discounted Cash Flow (DCF) analysis. According to Brennan & Schwartz (1985), mining should be evaluated by the stock market analogy due to the high level of uncertainty on its cash flow from the fluctuation of the commodity price. The method that is used to value the mining investment that is adapted from the stock option valuation in the secondary market is called the Real Option Valuation. Real Option Valuation used in this research is in form of a Least Square Monte Carlo (LSM) analysis. The LSM method utilizes the principals of monte carlo with the price variable as a factor of uncertainty in order to form the monte carlo path as the anticipation of price changes in the future and to determine the option value from the price variance that is formed against the cash flow used in the concept of Least Square. Using the method of real option, the management flexibility could be accommodated, including the decision to shut down the mining operation when the price is not compatible to the calculated projection. The research was started by generating 4 valuation algorithms which are the Weighted Average Cost of Capital (WACC), Discounted Cash Flow (DCF), volatility, and the Least Square Monte Carlo (LSM). Then, simulations were done for the entire algorithms beginning with the WACC, DCF, volatility, and LSM calculation that will be adjusted with the real life mining conditions. According to the LSM valuation results, the decision making on the mine abandonment using the LSM method with 8 monte carlo paths stated that only path number 2 and 5 could be used until the end of the mine operation life.